2019
DOI: 10.1155/2019/6751932
|View full text |Cite
|
Sign up to set email alerts
|

ECG-Based Subject Identification Using Statistical Features and Random Forest

Abstract: In this work, a nonfiducial electrocardiogram (ECG) identification algorithm based on statistical features and random forest classifier is presented. Two feature extraction approaches are investigated: direct and band-based approaches. In the former, eleven simple statistical features are directly extracted from a single-lead ECG signal segment. In the latter, the single-lead ECG signal is first decomposed into bands, and the statistical features are extracted from each segment of a given band and concatenated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Many proposals can also be found that use Machine Learning (ML) or DL algorithms to perform user identification and classification. Some of the most promising algorithms tested for user identification could be some of the ML algorithms such as Support Vectors Machine (SVM) [72,102,103], a Random Forest [104,105] or Logistic Regression [106,107], other deep learning algorithms as a k-Nearest Neighbour (k-NN) [108,109,110] or any Neural Network (NN) [93,111,112,113,114].…”
Section: The Process Of Ekg Identificationmentioning
confidence: 99%
“…Many proposals can also be found that use Machine Learning (ML) or DL algorithms to perform user identification and classification. Some of the most promising algorithms tested for user identification could be some of the ML algorithms such as Support Vectors Machine (SVM) [72,102,103], a Random Forest [104,105] or Logistic Regression [106,107], other deep learning algorithms as a k-Nearest Neighbour (k-NN) [108,109,110] or any Neural Network (NN) [93,111,112,113,114].…”
Section: The Process Of Ekg Identificationmentioning
confidence: 99%
“…Next, calculations were applied to the baseline removed pressure signal to create sixty-four features for each 250 ms epoch of the recordings. The 64 features were created using an ensemble of time domain statistical measures across different size windows, peak detection information and frequency domain measures [24,25]. The 64 features are split into 8 groups each with 8 features each to make it easier to describe in table II.…”
Section: F Masseter Pressure Algorithmmentioning
confidence: 99%
“…Statistical measures such as variance, skewness, and kurtosis of ECG signals are extracted as statistical features. The kurtosis measures the sharpness of the peak, whereas skewness is used to measure the asymmetry of the ECG signal's amplitude distribution (Alotaiby et al 2019). Depending on heart activity, sample distribution in ECG signal may vary.…”
Section: Statistical Featuresmentioning
confidence: 99%